2005
DOI: 10.1093/her/cyh063
|View full text |Cite
|
Sign up to set email alerts
|

Free school fruit--sustained effect 1 year later

Abstract: This study reports the effect of a school-randomized fruit and vegetable intervention consisting of a subscription to the Norwegian School Fruit Programme at no parental cost, and the Fruit and Vegetables Make the Marks (FVMM) educational programme, both delivered in the school year of 2001-02. Nine randomly chosen schools received the intervention and 10 schools served as control schools. Participating pupils completed questionnaires at baseline (September 2001), at Follow-up 1 (May-June 2002) and at Follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
141
1
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(156 citation statements)
references
References 12 publications
9
141
1
5
Order By: Relevance
“…This is in accordance with the findings of other intervention studies, such as the European Pro Children Study and the Norwegian Fruit and Vegetables Makes the Marks (FVMM) project, which observed somewhat higher effect sizes (20,21) at longer-term follow-up.…”
Section: Discussionsupporting
confidence: 91%
“…This is in accordance with the findings of other intervention studies, such as the European Pro Children Study and the Norwegian Fruit and Vegetables Makes the Marks (FVMM) project, which observed somewhat higher effect sizes (20,21) at longer-term follow-up.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier studies in which free fruit was added to school lunches have reported increased fruit intake (27)(28)(29) . One reason for the reduced food score registered in our study could be the different times during the year that registration took place.…”
Section: Discussionmentioning
confidence: 99%
“…Experiences from this last type of intervention -actual provision of F&V to the pupils -have generally been positive, although the evidence on whether it leads to sustained increases in F&V intake 2-3 years after the intervention period is both scarce and mixed (3,(8)(9)(10)(11) .…”
mentioning
confidence: 99%
“…These include pilot studies intending to map the potential effects of nationwide school fruit schemes (8,9,13) . In the USA, elementary schools with a high proportion of low-income students are eligible for receiving free school fruit through the Fresh Fruit and Vegetable Program.…”
mentioning
confidence: 99%